Analisa Air Circuit Breaker Mvs20n sebagai Sistem Proteksi Panel Accombiner di PT. Tiga Kreasi Indonesia - Apriliano Chandra Diva; Didik Aribowo (Jurnal Kendali Teknik dan Sains, 2026)
Air Circuit Breaker (ACB) is a protection device used in low- and medium-voltage panels, with air at atmospheric pressure functioning to extinguish arcs generated by switching processes or electrical disturbances. This study aims to analyze ACB components, wiring systems, threshold value calculations, and the electric tripping unit system. The research methods used include observation, interviews, and literature study. The results show that the ACB component testing produced an incoming current value of 2,000 A, with Ir set at 0.4, Lsd at 2, and Tr at 0.5. Based on these values, the ACB threshold limit is 800 A, while the Lsd current reaches 1,600 A. If the current passing through the ACB exceeds 1,600 A, the ACB will automatically trip and disconnect the circuit within 0.5 seconds. The pre-alarm is inactive at 85% because this position is the threshold point, while at 90% the pre-alarm becomes active as the current approaches the tripping threshold. Overall, the electrical tripping system activates automatically during overload or short-circuit conditions to protect the circuit.